Toward a Natural Classification of Botryosphaeriaceae: A Study of the Type Specimens of Botryosphaeria sensu lato - Zhang, Ying; Zhou, Yupei; Sun, Wei; Zhao, Lili; Pavlic-Zupanc, D.; Crous, Pedro W.; Slippers, Bernard; Dai, Yucheng (Frontiers in Microbiology, 2021)
The genus Botryosphaeria includes more than 200 epithets, but only the type species, B. dothidea and a dozen or more other species have been identified based on DNA sequence data. The taxonomic status of the other species remains unconfirmed because they lack either morphological information or DNA sequence data. In this study, types or authentic specimens of 16 “Botryosphaeria” species are reassessed to clarify their identity and phylogenetic position. nuDNA sequences of four regions, ITS, LSU, tef1-α and tub2, are analysed and considered in combination with morphological characteristics. Based on the multigene phylogeny and morphological characters, B. cruenta and B. hamamelidis are transferred to Neofusicoccum. The generic status of B. aterrima and B. mirabile is confirmed in Botryosphaeria. Botryosphaeria berengeriana var. weigeliae and B. berengeriana var. acerina are treated synonyms of B. dothidea. Botryosphaeria mucosa is transferred to Neodeightonia as N. mucosa, and B. ferruginea to Nothophoma as No. ferruginea. Botryosphaeria foliicola is reduced to synonymy with Phyllachorella micheliae. Botryosphaeria abuensis, B. aesculi, B. dasylirii and B. wisteriae are tentatively kept in Botryosphaeria sensu stricto until further phylogenetic analysis is carried out on verified specimens. The ordinal status of Botryosphaeria apocyni, B. gaubae and B. smilacinina cannot be determined, and tentatively accommodate these species in Dothideomycetes incertae sedis. The study demonstrates the significance of a polyphasic approach in characterizing type specimens, including the importance of using of DNA sequence data.